Estudo da atividade antinociceptiva e anti-inflamatória do monoterpeno a,b-Epoxi-carvona e seu efeito sobre a neurotransmissão glutamatérgica - Rocha, Marilene Lopes da (2010)
The a, b-epoxy-carvone (EC) monoterpene is found in many essential oils from plants, but can also be obtained through organic synthesis from the R-(-)-carvone. Previous studies have demonstrated that this compound exerts depressant effect on central nervous system (CNS), and is also known to have anticonvulsant effects, antioxidant and antimicrobial activities. This study investigated the antinociceptive and antiinflammatory effects of EC in adult male Swiss mice, as well as, its effect on glutamatergic neurotransmission in rats using behavioral tests, vascular permeability test, measurement of paw edema and electrophysiological recordings in vitro, respectively. Intraperiotoneal administration (ip) of EC at doses of 200 or 300 mg/kg provided a significant antinociceptive effect as shown in the writhing test induced by acetic acid. The EC also caused a reduction in formalin-induced nociception in the first (at 300 mg/ g) and second phase (at 200 or 300 mg/kg). In the hot plate test an increase in latency was found at 30 min (at 200 or 300 mg/kg) and 60 min (300 mg/kg) after administration of EC, the effect that was reversed by naloxone, an opioid receptor antagonist. After administration of EC (300 mg / kg), the increased vascular permeability induced by acetic acid was reduced, as well as the paw edema induced by carrageenan. The EC reduced by 70% the excitatory postsynaptic potentials (EPSP) field, as well as the glutamatergic EPSP of the pyramidal neurons from the CA1 hippocampal region and the neurons from the nucleus of the solitary tract (NTS). These results suggest that EC has peripheral and central antinociceptive activity in mice, probably related to opioid system activation and inhibition of acute inflammatory reaction. In addition, EC has depressant effects on excitatory postsynaptic neurotransmission.